Spectrophotometric Determination of Aztreonam in Bulk and its Pharmaceutical Formulations - Rasheed, Abdul; Ramachandran, D.; Begum, Jameelunnisa (Asian Journal of Chemistry, 2010)
Three simple and sensitive methods for the assay of aztreonam were developed. Methods A-C are based on the oxidation of aztreonam with an excess of oxidant [N-bromo succinamide (NBS) in methods A and B or chloramine T (CAT) in method C] in acidic medium. The unreacted oxidant is then estimated by using a oxidisable dye [celestine blue (CB) in method A or gallocyanine (GC) in method C] or p-N-methyl amino phenyl sulphate (PMAP)-sulphanilamide (SA) reagent in method B. Regression analysis of Beer’s law plots showed good correlation in the concentration ragne of 4-20, 4-20 and 4-20 μg/mL for method A, B and C, respectivley. The results of analysis have been validated statically and by recovery studies.